Molecular Characterization of a Spontaneous Waxy Starch Mutation in Cassava - Aiemnaka, Pornsak; Wongkaew, Arunee; Chanthaworn, Jumnong; Nagashima,Sathakupt Ken; Boonma, Supawadee; Authapun, Jetsada; Jenweerawat, Sujin; Kongsila, Pasajee; Kittipadakul, Piya; Nakasathien, Sutkhet; Sreewongchai, Tanee; Wannarat, Wannasiri; et al. (Wiley, 2012)
Cassava (Manihot esculenta Crantz) starch is traded in international markets more than starch from any other source. The starch industry requires cassava cultivars with novel starch characteristics for commercial exploitation. A natural source of waxy (amylose‐free) cassava starch, clone AM 206‐5, was identified at the International Center for Tropical Agriculture (CIAT). The granule‐bound starch synthase I (GBSSI) gene is related to the waxy starch trait. The objectives of this study were to introgress the waxy starch mutation into Thailand's cassava breeding populations, to analyze the inheritance of waxy starch in cassava, and to develop molecular markers for this trait. AM 206‐5 (wxwx) was crossed with several elite cultivars (WxWx) to transfer the wx allele. Unrelated “F1” (Wxwx) genotypes were crossed among themselves to produce a “F2” segregating population with negligible levels of inbreeding depression. The waxy starch phenotype was recovered in 25.7% of the 11,192 genotypes tested. This result provides further evidence that cassava is a functional diploid and that only one copy of GBSSI is present in cassava. A full‐length genomic DNA sequence of GBSSI was isolated and characterized from C8, a waxy starch “F2” clone derived from AM 206‐5. We exploited these sequence differences to develop two diagnostic single‐nucleotide‐amplified polymorphism (SNAP) markers to differentiate homozygous waxy (wxwx) from the heterozygous (Wxwx) and homozygous (WxWx) nonwaxy genotypes.